Design of mesoscopic photonic crystal waveguides. Issue 6 (16th May 2019) - Ferrara, Benedetta; Grande, Marco; Calò, Giovanna; D'Orazio, Antonella; Petruzzelli, Vincenzo; Dagens, Beatrice; Monmayrant, Antoine; Gauthier‐Lafaye, Olivier; Magno, Giovanni
Abstract : The authors numerically analyse the performance of a mesoscopic photonic crystal (MPhC) waveguide that could be exploited to develop a new class of routing elements and a cascadable circuitry taking advantage of the spatial and spectral reconfigurability that this structure offers. The design of the MPhC was performed by means of the 3D plane wave expansion method (3D‐MPB code), while the MPhC waveguide has been analysed by a 3D‐FDTD code. The numerical results show that the MPhC waveguide exhibits minimal reflections at PhC input interfaces without either affecting the feasibility or the complexity of the structure, high transmission, strong mesoscopic self‐collimation and discrete translational invariance. Moreover, the influence of the characteristics of the Gaussian source on the collimation phenomenon has been explored by considering different values of the waist radius.